Iterative Development of In This together, the First mHealth HIV Prevention Program for Older Adolescents in Uganda - Ybarra, Michele L.; Agaba, Edgar; Chen, Emilie; Nyemara, Novatus (AIDS and Behavior, 2020)
In Uganda, HIV prevention programming for older adolescents is noticeably lacking, even though HIV incidence rates increase dramatically from adolescence into young adulthood. Here we describe the development of In This together (ITG), the first-of-its-kind, comprehensive text messaging-based HIV prevention program for both sexually active and abstinent 18- to 22-year-old Ugandans. Five iterative development activities are described: (1) conducting focus groups (FGs) to better understand the sexual decision-making of older adolescents across Uganda and to gain ‘voice’ of older adolescents; (2) the drafting of intervention content based on FG data; (3) testing of the drafted content with two Content Advisory Teams (CATs) that reviewed and provided feedback on the messages; (4) alpha-testing the program among the research team; and (5) beta-testing the intervention and protocol with people in the target population. Participants were recruitment nationally via Facebook and Instagram, and enrolled over the telephone by research staff. Results suggest that men were easier to reach and engage across all intervention development steps. As such, specific efforts to enroll women were made to ensure that feedback from both sexes was taken into account. FG participants said they were interested in learning more about sexual positions, how to prepare for sex, the consequences of unprotected sex, benefits of protected sex, masturbation, and how to be a good sexual partner. In both the FGs (n = 202) and CATs (n = 143) however, some noted that masturbation, oral sex, and anal sex were particularly sensitive topics. These messages were rewritten to address the cultural sensitivity. Feedback from beta test participants (n = 34) suggested that text messaging-based HIV prevention programming that is intense (e.g., 5–11 messages per day) and extends for two months, is both feasible and acceptable. In conclusion, the engagement of older adolescents at each step of the iterative intervention development process increased the likelihood that the final product would resonate with 18- to 22-year-old Ugandan youth across the country. Furthermore, social media appears to be a feasible method for recruiting national samples of Ugandan older adolescents into HIV-focused research.
Keywords: HIV prevention; Older adolescents; mHealth; Uganda; Sub-Saharan Africa; Intervention development